A study of Paraoxonase-1 192 gene polymorphism in coronary artery disease - Muhammad Musa, Nurul Ashikin; Abdullah, Nor Zamzila; A.Talib, Norlelawati; Nik Ahmad, Nik Nur Fatnoon (2013)
Paraoxonase-1 (PON-1) is an HDL-associated enzyme which has been implicated in the pathogenesis of atherosclerosis by preventing lipid peroxide generation. The population variability in this enzyme activity is attributed to polymorphism in PON-1 gene. Recent studies have suggested that PON-1 Q192R polymorphism is associated with coronary artery disease (CAD) in different ethnic populations. However to this date, there is no such study in Malaysia. The present study looks at PON-1 Q192R gene polymorphism among CAD patients and healthy controls in Kuantan, Pahang. This study consisted of 187 CAD patients and 188 healthy subjects. PON-1 Q192R genotypes were determined by polymerase chain reaction (PCR) and AlwI restriction enzyme digestion. The Q192R polymorphism was significantly associated with CAD (p = 0.004), where the 192R allele was found to be more frequent in CAD patients than controls (0.618 vs 0.513) with QR genotype being the commonest (45.5%), followed by RR (39.0%) and QQ (15.5%) genotypes. In conclusion, the PON-1 Q192R polymorphism is significantly associated with CAD. This finding indicates that this gene variation is a useful genetic marker for CAD in our population. However, a multicentre study may be required to confirm our findings in Malaysian population.